2018
DOI: 10.1038/s41598-018-29833-5
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of Albumin-to-Alkaline Phosphatase Ratio in upper tract urothelial carcinoma

Abstract: To assess the prognostic impact of pretreatment albumin-to-alkaline phosphatase ratio (AAPR) in patients with upper tract urothelial carcinoma (UTUC), the data of 692 patients, operated between 2003 and 2016 in our center, were retrospectively assessed. The threshold of AAPR was defined as 0.58 by using the receiver-operating curve analysis. Overall survival (OS), cancer-specific survival (CSS), and recurrence-free survival (RFS) were evaluated using the Kaplan-Meier method. And the univariate and multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 23 publications
4
55
1
Order By: Relevance
“…first reported the prognostic value of the AAPR and revealed that the AAPR was a significant prognostic predictor in hepatocellular carcinoma (HCC) . Similar studies have been subsequently reported in other types of cancers, including small cell lung cancer (SCLC) . However, the prognostic value of the AAPR has not yet been well studied in non‐small cell lung cancer (NSCLC) patients.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…first reported the prognostic value of the AAPR and revealed that the AAPR was a significant prognostic predictor in hepatocellular carcinoma (HCC) . Similar studies have been subsequently reported in other types of cancers, including small cell lung cancer (SCLC) . However, the prognostic value of the AAPR has not yet been well studied in non‐small cell lung cancer (NSCLC) patients.…”
Section: Introductionmentioning
confidence: 74%
“…the AAPR was found to be an independent prognostic factor for OS and DFS in patients with HCC regardless of the treatment approach . Since then, the AAPR has been proven to be a significant prognostic predictor for nasopharyngeal carcinoma, SCLC, and upper tract urothelial carcinoma (UTUC), whereas it has not yet been explored in patients with NSCLC …”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the low AAPR contributed to worse survival outcomes in well and moderate differentiated cervical cancer; but in terms of poorly differentiated disease, there was no significant relationship between them, which was consistent with the result obtained in upper tract urothelial carcinoma. 39 The result gave us a prompt that patients with low AAPR level should have their cancer status and physical condition evaluated more carefully compared with the high-AAPR group, especially in well and moderate differentiated patients. In our study, adjuvant therapy was found to be an independent prognostic index for OS and DFS.…”
Section: Discussionmentioning
confidence: 99%
“…36 Prior studies have shown that nutrient deficiency and systematic inflammatory response might play a critical role in the pathogenesis and progression of human carcinomas and were correlated with inferior prognosis in patients undergoing resection for solid tumors. 8,[37][38][39] Zheng et al have demonstrated that ALB is an independent prognostic indicator in early operable cervical cancer. 40 Moreover, a recent published article found that high levels of ALP could influence tumorigenesis and predict outcomes in cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the included studies were shown in Table 1. In the current research, 15 retrospective articles with 6,062 cancer patients were included [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Because of the subgroup analysis in three articles [15,17,19], we regarded them as 2 or 3 independent studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%